IDNLearn.com offers a user-friendly platform for finding and sharing answers. Discover the reliable solutions you need with help from our comprehensive and accurate Q&A platform.
Sagot :
Answer:
c = -9
Step-by-step explanation:
4c + 11 = -25
4c = -25 - 11
4c = -36
c = -36 : 4
c = -9
or
4c + 11 + 25 = 0
4c + 36 = 0
c = (-36)/4
c = -9
-------------------
check
4 *(-9) + 11 = -25
-36 + 11 = -25
-25 = -25
the answer is good
Answer:
c= -9
Step-by-step explanation:
1. 4c + 11 = -25
2. Put all like terms together and change the sign. In this case, the +11 will go to the right with the -25 and it will become -11.
Therefore:
4c= -25 -11
4c= -36
3. Make c the subject. Since 4 is being multiplied by c, when it goes to the right, it will divide.
Therefore:
c= -36/4
c= -9
We are happy to have you as part of our community. Keep asking, answering, and sharing your insights. Together, we can create a valuable knowledge resource. Thank you for visiting IDNLearn.com. We’re here to provide clear and concise answers, so visit us again soon.